i-KAM: an improved software project monitoring task model of Agile Kanban - Al-Aidaros, Hamzah Ali Alawi (2021)
Kanban is one of the Agile methods that has being widely adopted in Software Project Management (SPM). However, Kanban displays some shortcomings, specifically in the progress monitoring task, which are an inadequate technique for effective project progress tracking, difficulty to determine the optimum Work In Progress (WIP) limits, and insufficient information to visualize project progress of software development projects. These issues have caused negative impacts on the success of software projects as the delays in project scheduling lead to late deliveries. Therefore, this study aims to propose an improved software project monitoring task model of the Agile Kanban (i-KAM). This study was conducted in three main phases. Firstly, a theoretical study was performed to identify the components and their relevant criteria that influence the software project’s monitoring task. Secondly, the proposed model was constructed based on the content and comparative analysis results of the three main components including their influencing criteria; progress tracking extension, optimum WIP limits generation, and workflow visualization. Then, the verification of the model was done via an expert review method involving five knowledge and six domain experts. Finally, a Progress Monitoring Prototype Tool (PM-PT) was designed and developed to evaluate the applicability of i-KAM, while its effectiveness was evaluated by seven software practitioners through a focus group discussion. In addition, two case studies were conducted to practically validate i-KAM using PM-PT in actual projects within two different software organizations. The findings indicate that i-KAM improves the progress monitoring task of the Agile Kanban by extending its tracking mechanism, controlling WIP limits, and providing useful insights regarding project status. Furthermore, software practitioners affirmed that i-KAM is an effective model with easy and practical implementation. Theoretically, this study contributes to improve the software project monitoring task of Agile Kanban. The model helps both software developers and project managers in effectively monitoring software projects’ progress as well as to make meaningful decisions in software development projects.